A new perspective in avian bone health: dietary supplementation with a standardized dry grape extract improves pullets’ bones’ quality through metabolic modulation - Fatima Zohra Aberkane; Paul Engler; Severine Boisard; Mohamed El Amine Benarbia; David Guilet (Poultry Science)
In laying hens, maintaining optimal bone health and development from the early stages is crucial, as it directly affects their egg-laying efficiency, overall welfare and productivity. Studies have shown that grape polyphenols from Vitis vinifera enhance bone health in both humans and animals. Still, the mechanisms behind this effect remain unclear, given the diversity of grape polyphenols and their varying mechanisms of action. The objective of this study was to investigate the effect of a standardized dry grape extract (SDGE) on bone quality and metabolome of future laying hens reared in commercial conditions. Therefore, 36300 day-old pullets were randomly divided into two barns on the same farm site. Both received the same diet, with the addition of 30 mg/kg of SDGE (Nor-Grape®, Nor-Feed, France) from day 1 until week 17 in the supplemented group (SDGE). At the end of the supplementation period, several bone quality parameters were analyzed on 50 individuals per group. Additionally, non-targeted metabolomics on plasma and bones were performed to uncover the impact of SDGE supplementation on pullet’s metabolome. Results demonstrated that keel bone deformity tended to improve following SDGE supplementation (P = 0.10). Moreover, SDGE intake significantly increased bone dry and mineral content, compared to the control group (P < 0.05) and tended to increase calcium (Ca) (P = 0.074) and phosphorus (P) content (P = 0.055). On the other hand, non-targeted metabolomics on plasma samples revealed an impact on fatty acids and glycerophospholipid metabolisms while bone samples analysis uncovered pathways related to sphingolipid and estrogen mediated signaling pathways. Overall, this study suggests novel mechanisms related to estrogen signaling through lipid metabolism in SDGE supplemented pullets and highlights that nutritional intervention with SDGE in early developmental stage of future laying hens improves their bone health prior to entry into the laying phase, thus proving a useful tool in bone health management.